Meson properties at finite temperature in a three flavor nonlocal chiral quark model with Polyakov loop - Contrera, Gustavo Aníbal (2010)
We study the finite temperature behavior of light scalar and pseudoscalar meson properties in the context of a three-flavor nonlocal chiral quark model. The model includes mixing with active strangeness degrees of freedom, and takes care of the effect of gauge interactions by coupling the quarks with the Polyakov loop. We analyze the chiral restoration and deconfinement transitions, as well as the temperature dependence of meson masses, mixing angles and decay constants. The critical temperature is found to be Tc ≃ 202 MeV, in better agreement with lattice results than the value recently obtained in the local SU(3) PNJL model. It is seen that above Tc pseudoscalar meson masses get increased, becoming degenerate with the masses of their chiral partners. The temperatures at which this matching occurs depend on the strange quark composition of the corresponding mesons. The topological susceptibility shows a sharp decrease after the chiral transition, signalling the vanishing of the U(1)TA anomaly for large temperatures.